Prospective comparison of a PCR assay and a microbiological culture technique for identification of pathogens from blood and non-blood samples in septic patients. Issue 1 (December 2015) - Plettig, Runa; Nowak, Andreas; Balau, Veronika; Hahnenkamp, Klaus; Usichenko, Taras
Abstract Background Molecular amplification techniques are suggested to be a useful adjunct in early detection of pathogens in septic patients. The aim was to study the feasibility of a polymerase chain reaction (PCR) assay compared to the standard microbiological culture (MC) technique in identification of pathogenic microorganisms from blood and non-blood samples in septic patients. Methods Samples for pathogen identification were taken during febrile septic episodes (SE) in 54 patients with sepsis and analyzed using both MC and PCR. Semi-automated multiplex PCR, provided by Philips Medical Systems, was able to detect nine different pathogens. The accuracy of pathogen identification using PCR vs. MC as well as the time-saving effect of PCR on the potential decision-making process for antimicrobial therapy was evaluated. Results In a total of 258 samples taken during 87 SE, both methods yielded more pathogens from the non-blood than blood samples (87 % vs. 45 %;p  = 0.002). PCR identified more pathogens than MC in the blood samples (98 vs. 21;p  < 0.0001), but not in other body fluids. In 35 SE, the potential decision on appropriate antimicrobial therapy based on PCR results could have been made 50 (median; interquartile range 35–87) hours earlier than decisions based on standard MC. Conclusions In septic patients, multiplex PCR identified more pathogenic microorganisms isolated from the blood samples than the standard MC technique. In the non-blood samples, PCR was comparable to that of MC.